A recombinant DNA‐satellite associated with Pepper yellow leaf curl Indonesia virus in highland area - Argawi Kandito; Sedyo Hartono; Sri Sulandari; Susamto Somowiyarjo (Indonesian Journal of Biotechnology, 2021)
Yellow curl disease caused by begomovirus is a major threat for horticulture in Indonesia. Control mea‐ sures for the disease face several constraints, one of which is the association between begomovirus and DNA satellites which can affect the severity of symptoms. In this study, we detected the presence of a DNA satellite associated with begomovirus in a highland area. The sample was obtained from Ketep, Magelang, located approximately 1400 meters above sea level. Begomovirus was detected using primers PAL1V1978/PAR1C715 that resulted in an amplicon of ap‐ proximately 1600bp. The presence of this satellite was detected using primers CLB36F/CLB37R, resulting in full‐length satellite genome of approximately 1300bp. Sequence analysis showed the sample was infected by Pepper yellow leaf curl Indonesia virus (PepYLCIV) and a non‐coding satellite which resembled some characteristics of common betasatellites with imperfect putative ORF βC1. SimPlot analysis revealed the recombination event between betasatellites and DNA‐B of PepYLCIV. The satellite found in this study is thought to be the result of recombination due to multiple infections in plants.